In Vitro Antigenotoxic, Antihelminthic and Antioxidant Potentials Based on the Extracted Metabolites from Lichen, Candelariella vitellina - Islam El-Garawani; Mahmoud Emam; Waill Elkhateeb; Hesham El-Seedi; Shaden Khalifa; Salwa Oshiba; Shaimaa Abou-Ghanima; Ghoson Daba (MDPI AG, 2020)
Lichens have recently received great attention due to their pharmacological potentials. The antigenotoxic potential of C. vitellina extract (25 and 50 µg/mL) was assessed in normal human peripheral blood lymphocytes (HPBL) against Mitomycin C (MMC) co-treatments. Flow cytometric analyses of cell cycle distribution, as well as apoptosis (Annexin V/PI), revealed that the extract had significantly (p ≤ 0.05) ameliorated the MMC toxicity by reducing the apoptotic cells and normalized the cell cycle phases. C. vitellina exhibited antigenotoxicity by ameliorating the diminished mitotic index and DNA single-strand breaks caused by MMC. Herein, the hydromethanolic extract (80%) of Candelariella vitellina (Japan) lichen, exhibited very low cytotoxicity towards normal human peripheral lymphocytes (HPBL) with IC50 >1000 µg/mL. In order to explore the antihelminthic effect, Echinococcus granulosus protoscoleces were used in vitro. Eosin staining revealed significant (p ≤ 0.05) dose and time-dependent scolicidal effects of the extract confirmed by degenerative alterations as observed by electron scan microscopy. Furthermore, primary and secondary metabolites were investigated using GC-MS and qualitative HPLC, revealing the presence of sugars, alcohols, different phenolic acids and light flavonoids. Significant antioxidant capacities were also demonstrated by DPPH radical-scavenging assay. In conclusion, the promising antigenotoxic, antihelminthic and antioxidant potentials of C. vitellina extract encourage further studies to evaluate its possible therapeutic potency.